Association Between Endometriosis and Subsequent Risk of Sjögren’s Syndrome: A Nationwide Population-Based Cohort Study - Chao, Yung-Hsiang; Liu, Chin-Hsiu; Pan, Yu-An; Yen, Fu-Shun; Chiou, Jeng-Yuan; Wei, James Cheng-Chung (Frontiers in Immunology, 2022)
Objective: The relationship between endometriosis and the ensuing risk of Sjögren’s syndrome has remained unclear. This study aims to present epidemiological evidence for this connection. Methods: This is a retrospective cohort study of endometriosis patients (ICD-9-CM 617.0-617.9 and 621.3) and matched comparison group between 2000 and 2012 in the National Taiwan Insurance Research Database. After age matching, we analyzed the association between endometriosis and Sjögren’s syndrome (ICD-9-CM 710.2). We used the Cox proportional hazard model to examine the hazard ratio of incidental Sjögren’s syndrome. Subgroup analyses on age, comorbidities, and disease duration were also performed. Results: A total of 73,665 individuals were included in this study. We identified 14733 newly diagnosed endometriosis patients and 58,932 non-endometriosis comparison group. The adjusted hazard ratio (HR) for incidental Sjögren’s syndrome was 1.45 (95% confidence interval CI=1.27-1.65) in the endometriosis group, compared to the non-endometriosis comparison group. In subgroup analysis, the adjusted HR was 1.53 (95% CI=1.25-1.88) in the age group of 20-39 and 1.41 (95% CI =1.18-1.68) in the age of 40-64. Time-vary analysis showed that endometriosis who have a follow-up time of fewer than five years (adjusted HR=1.57, 95% CI=1.32-1.87) have a significantly highest risk of having subsequent Sjögren’s syndrome. Conclusion: This population-based cohort study indicated that having a history of endometriosis puts patients at an increased risk of getting Sjögren’s syndrome afterward, especially in the age group of 20-39 and within the first five years after the diagnosis of endometriosis. Clinicians should recognize this possible association in managing endometriosis or Sjögren’s syndrome patients.